2013
DOI: 10.1111/1462-2920.12178
|View full text |Cite
|
Sign up to set email alerts
|

Functional and compositional succession of bacterioplankton in response to a gradient in bioavailable dissolved organic carbon

Abstract: Studies indicate that bacterial taxa utilize different fractions of the dissolved organic carbon (DOC) pool, while others suggest functional redundancy among constituents of bacterioplankton, implying only a weak coupling between community structure and function. We examined bacterial compositional and functional [ectoenzymatic activities and growth efficiency; bacterial growth efficiency (BGE)] responses to a gradient in bioavailable DOC (bDOC). This was achieved over 10 days in DOC utilization assays contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
50
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 69 publications
14
50
0
Order By: Relevance
“…Pelagibacteraceae (also known as the SAR11 clade) is a family of extreme oligotrophs that are widely distributed over the Earth's oceans (62). The abundance of the Pelagibacteraceae has been shown to decrease in cases of increasing DOC (63,64), bacterial cell density (63), and Chl-␣ fluorescence (65) in the water column, in accordance with our findings. The SAR86 clade is also abundant in the surface ocean and shares many genome-wide characteristics with the Pelagibacteraceae family (66).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Pelagibacteraceae (also known as the SAR11 clade) is a family of extreme oligotrophs that are widely distributed over the Earth's oceans (62). The abundance of the Pelagibacteraceae has been shown to decrease in cases of increasing DOC (63,64), bacterial cell density (63), and Chl-␣ fluorescence (65) in the water column, in accordance with our findings. The SAR86 clade is also abundant in the surface ocean and shares many genome-wide characteristics with the Pelagibacteraceae family (66).…”
Section: Discussionsupporting
confidence: 89%
“…Our results agree with the latter, demonstrating a consistent trend toward a decrease in the abundance of the SAR86 clade at the impacted sites, similar to the findings for the Pelagibacteraceae family. The Alteromonadaceae family has been associated with increased organic carbon levels (64,70,71), whereas the Rhodobacteraceae and Cryomorphaceae have been associated with phytoplankton-derived organic matter decomposition at the late stages of phytoplankton blooms (68,70,(72)(73)(74). Our findings corroborate these observations, as the abundance of the Alteromonadaceae was mostly increased in the impacted samples from Sitia, where the DOC content was the highest, and the abundance of the Rhodobacteraceae was increased in impacted samples at Agios Nikolaos, where Chl-␣ levels were the highest and phytoplankton blooms have occurred in the past.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Condon et al (2011) observed that the rapid increase of bacterial metabolism in response to the addition of DOM released by a jellyfish was accompanied by a significant decline of BGE by 10 to 15 % compared to the control treatment. Dinasquet et al (2013) observed a similar BGE (30-40 %) for bacterial communities exposed or not to DOM from the ctenophore Mnemiopsis leidyi. These contrasting observations may result from differences in experimental setup and bacterial community composition in these studies.…”
Section: Discussionmentioning
confidence: 52%
“…Rates of decomposition of both excretion and dead jellyfish biomass result in a large input of nutrients in the marine environment West et al 2009;Tinta et al 2010). Recent studies also reported a change in the bacterial structure in response to the use of organic matter from jellyfish for different coastal waters (Tinta et al 2010(Tinta et al , 2012Condon et al 2011;Dinasquet et al 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Bacterioplankton communities while probably more sensitive to changes in environmental conditions are also subject to living in a highly dynamic environment. Bacterioplankton composition though has been shown to vary Table 2 along pronounced environmental gradients of carbon, temperature and salinity [58,59].…”
Section: Bacterial Composition: Biotope Versus Environmentmentioning
confidence: 99%